Sleep duration in school-age children with epilepsy: A cross-sectional study - Karthikeyan, Aishwarya; Srinivasan, Thiagarajan; Chandrasekaran, Venkatesh; Subramanian, Mahadevan (Indian Journal of Child Health, 2018)
Background: Normal sleep is required for the optimal growth and development of the children. Ineffective or inadequate sleep is common in children with epilepsy. Objectives: The objectives of this study were to study the sleep duration and describe the factors affecting it in school-aged children with epilepsy attending the seizure clinic of a pediatric tertiary care hospital. Materials and Methods: 6–12-year-old children with epilepsy, attending the seizure clinic formed the study subjects. They were assessed for inclusion in the study using INCLEN diagnostic tool for epilepsy (INDT-Epi) to achieve a sample size of 139. Informed written consent was obtained from parents. Background sociodemographic information, seizure type and treatment details, and duration of sleep of the child were collected from the parents. The proportion of children with epilepsy who had sleep problems were expressed as percentage. Results: The mean age of study population was 9.07±2.09 years. The average sleep duration of the study population was 9.41±1.41 h. The mean nap time of the study population was 68.51±33.88 min. No significant association was seen among the factors that determine sleep duration. Conclusion: Children with epilepsy tend to sleep for lesser hours when compared to historic controls of normal school-age children reported in literature.